World War, 1939-1945
Images document the effect of World War II on civilian life in Pennsylvania with emphasis on Philadelphia. Portrays Russian prisoners of war at Fort Dix, and German POWs at camp near Kane, Pa., in a Philadelphia compound, and at Valley Forge General Hospital. Kane views depict barracks and men working and eating. Contains views of German and Italian aliens leaving a bus to go into barred cars that will take them to a camp in Butte, Montana. Shows ships from Holland, Norway, Greece, Panama, England, and Italy that have been intered at Port Richmond. Illustrates parades honoring war heroes in Philadelphia and Pittsburgh. The Philadelphia parade began at Northeast Airport and concluded with ceremonies at the liberty bell and Independence Hall. Many images show the ticker tape parade as the heroes passed City Hall. Cocuments civilian response to the surrender of Germany, Japan, and Italy. Portrays people kissing, hugging, praying, dancing in the streets, throwing ticker tape, and burning Hirohito in effigy. Also depicts an exhibition of Army surplus materials at the supply depot. Oversize is an ad to enlist Civil Defense volunteers. It shows the Philadelphia skyline with planes super-imposed, bombing the city.